PENGARUH PELAKSANAAN KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP KEPUASAN KERJA PERAWAT (Studi Kasus Rumah Sakit Umum Daerah (RSUD) Arifin Achmad Pekanbaru) - Deni Nurhidayanti; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Research Aims To Know How to Influence the Implementation of Safety and Health at Work (K3) on Job Satisfaction Nurses (Case Study Regional General Hospital (Hospital) Arifin Achmad Pekanbaru) and how the implementation of safety and health do.The population in this study were nurses at the General Hospital (Hospital) Arifin Achmad Pekanbaru with sampling as many as 80 nurses using a formula Slovin. The research data in the form of primary data by questionnaire sebaga and secondary research instrument in the form of hospital archives. Analysis of the data used is to use statistical analysis with SPSS.According to the research conducted by the author take a conclusion Effect of Implementation of Safety and Health at Work (K3) on Job Satisfaction Nurses (Case Study Regional General Hospital (Hospital) Arifin Achmad Pekanbaru) of respondents who researched that each have indicator interrelated and keselamata and positive influence on the health of nurse Job Satisfaction (Case Study Regional General Hospital (Hospital) Arifin Achmad Pekanbaru).Keywords: Occupational Safety and Health, Job Satisfaction